Turning knowledge into value in professional service firms - Forstenlechner, Ingo; Lettice, Fiona; Bourne, Mike; Webb, Carol (Emerald Group Publishing Limited, 2007)
Abstract: Purpose – The purpose of this paper is to present and discuss the findings of research into the value perception of knowledge management among lawyers and staff from among the top ten global law firms. Design/methodology/ approach – Interviews were conducted with lawyers as well as knowledge management (KM) service providers within the selected law firms. The results were then analysed by statistical means and compared to previous findings in literature. The methodology is inspired and broadly based on a research paper into the value perception of information by Broady-Preston and Williams. Findings – The findings are that respondents showed strong support for the value of KM to law firm success through concepts such as improved efficiency, quality and other drivers for better performance. Research limitations/implications – The survey in the paper itself was limited to the top ten global law firms and is therefore not representative of the entire professional service sector or the law firm sector. Practical implications – The results in the paper indicate strong support from the internal customer side for the notion of KM adding value to the business of a law firm. Originality/value – Prior to this paper there has been little research into the value perception of knowledge management within the professional service
Keywords: Value added; Knowledge management; Lawyers; Legal profession; Professional services